All-solid-state asymmetric supercapacitors based on ZnO quantum dots/carbon/CNT and porous N-doped carbon/CNT electrodes derived from a single ZIF-8/CNT template. Issue 26 (16th June 2016) - Zhang, Yidong; Lin, Baoping; Wang, Junchuan; Tian, Jiahui; Sun, Ying; Zhang, Xueqin; Yang, Hong
Abstract : Selectively converting a single MOF/CNT template into ZnO quantum dots/carbon/CNTs and porous N-doped carbon/CNTs for all-solid-state asymmetric supercapacitors. Abstract : Currently, the development of two kinds of materials from a single precursor has been an important frontier in material synthesis. In this study, we have successfully fabricated a single precursor using metal–organic frameworks (MOFs) (zeolitic imidazolate framework, ZIF-8) and carbon nanotubes (CNTs). ZnO quantum dots (QDs)/carbon/CNTs and porous N-doped carbon/CNTs have been selectively synthesized from a single ZIF-8/CNTs template. When the two derived materials were used for supercapacitor electrodes, they showed high capacitance values (185 F g −1 g for ZnO QDs/carbon/CNTs at 0.5 A g −1 and 250 F g −1 g for porous N-doped carbon/CNTs at 1 A g −1, respectively). Further, an all-solid-state asymmetric supercapacitor (ASC) device using ZnO QDs/carbon/CNTs as the positive electrode and porous N-doped carbon/CNTs as the negative electrode was fabricated, and this device could reach a working potential of 1.7 V, delivering a maximum energy density of 23.6 W h kg −1 and a maximum power density of 16.9 kW kg −1, which are better than those of the ZnO-based symmetric or asymmetric supercapacitor devices.